Interações sociais e dinâmicas comunicacionais nos games - ASSIS, Bruno Monte de (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
This article has like main goal to reflect about the interaction practices developed in the games, it having as an empirical component the game Ragnaraök Online – BRO. One of the principal motivations about the act of the play the game is the interaction between of the players mediated games (game as social activity), what highlights the communicative character of the game from the actions of the players. Our proposal, seek to understand, this way, the potentialities about the actions from of the players while in interaction with the game, like processes modifiers in different graduations in the experience with the midiatic product. BRO, allows interaction between players and they with the real world, transforming it and transforming themselves, of the form that both are mediator agents, doing emerge new cultural practices permeated by those interactions as in the virtual environment as real environment.